Overcoming treatment challenges in myelofibrosis and polycythemia vera: the role of ruxolitinib - Bryan, Jeffrey C. (Cancer Chemother Pharmacol, 2016)
Myelofibrosis (MF) and polycythemia vera (PV) are BCR-ABL1-negative myeloproliferative neoplasms associated with somatic hematopoietic stem cell mutations leading to over activation of JAK–STAT signaling. MF and PV are pathogenically related and share specific clinical features such as splenomegaly and constitutional symptoms. The MF phenotype is dominated by the effects of progressive bone marrow fibrosis resulting in shortened survival. In contrast, elevated thrombosis risk due to erythrocytosis is the primary clinical concern in PV. Ruxolitinib, an oral JAK1/JAK2 inhibitor, is approved in the USA for the treatment of patients with intermediate- or high-risk MF and patients with PV who have had an inadequate response to or are intolerant of hydroxyurea. For MF, results of two phase III studies demonstrated that ruxolitinib therapy reduced spleen volume and MF-related symptom burden, improved quality-of-life measures, and was associated with prolonged overall survival. Treatment benefits were generally sustained with continued therapy. Dose-dependent cytopenias were common but generally manageable with transfusions (for anemia), dose reduction, or treatment interruption. Optimal dosing management is critical to maintain long-term treatment benefit, because cessation of therapy resulted in rapid return of symptoms to baseline levels. Results of the phase III PV trial showed that ruxolitinib was significantly more effective than standard therapy in controlling hematocrit levels and improving splenomegaly and PV-related symptoms. Only 1 of 110 patients in the ruxolitinib arm compared with 6 of 112 patients in the control arm experienced a thromboembolic event through week 32. Grade ≥3 cytopenias were uncommon.